Effect of Date of Collection and Pod Length on Germination and Initial Seedling Growth of Albizia lebbeck (Benth.) - Malla, Suman; Shukla, Gopal; Chakravarty, Sumit (Indian Forester, 2013)
An experiment consisting of four dates of collection (9th February, 19th February, 1st March and 11th March) and three pod lengths (less than 10, 10-20 and more than 20 cm) were analyzed to study the effect on germination and initial growth of seedlings of Albizia lebbeck (Benth.) at Pundibari, West Bengal, India during February to July 2007. It was found that th pods collected on 19th February having length 10-20 cm gave significantly higher germination and initial seedling growth.